Culinary Versus Gastronomy - Soeroso, Amiluhur; Turgarini, Dewi (E-Journal of Tourism; Volume 7 Number 2 (September 2020), 2020)
Food becomes one of main income of tourism sector which supports Gross Domestic Product. Food and beverage is also suspected to be the tourists’ motivation for travelling. People, publicly, and government recognize it more as culinary. However, there is a view that argumentation which is constructed by public seems to be not accordance with the real situation. Gastronomy, which accommodates foodshed, cooking, until foodscape and human behaviour, is perceived to be more appropriate as a comparison argument. Related to that matter, in this paper, researcher is trying to study and to compare two-sided definition of terminology over culinary and gastronomy as a way to eliminate argumentum ad populum. Keywords: culinary, gastronomy, foodshed, foodscape, argumentum ad populum